In Silico Study of Superoxide Dismutase Gene Family in Potato and Effects of Elevated Temperature and Salicylic Acid on Gene Expression - Jelena Rudić; Milan B. Dragićević; Ivana Momčilović; Ana D. Simonović; Danijel Pantelić (Antioxidants, 2022)
Potato (Solanum tuberosum L.) is the most important vegetable crop globally and is very susceptible to high ambient temperatures. Since heat stress causes the accumulation of reactive oxygen species (ROS), investigations regarding major enzymatic components of the antioxidative system are of the essence. Superoxide dismutases (SODs) represent the first line of defense against ROS but detailed in silico analysis and characterization of the potato SOD gene family have not been performed thus far. We have analyzed eight functional SOD genes, three StCuZnSODs, one StMnSOD, and four StFeSODs, annotated in the updated version of potato genome (Spud DB DM v6.1). The StSOD genes and their respective proteins were analyzed in silico to determine the exon-intron organization, splice variants, cis-regulatory promoter elements, conserved domains, signals for subcellular targeting, 3D-structures, and phylogenetic relations. Quantitative PCR analysis revealed higher induction of StCuZnSODs (the major potato SODs) and StFeSOD3 in thermotolerant cultivar Désirée than in thermosensitive Agria and Kennebec during long-term exposure to elevated temperature. StMnSOD was constitutively expressed, while expression of StFeSODs was cultivar-dependent. The effects of salicylic acid (10−5 M) on StSODs expression were minor. Our results provide the basis for further research on StSODs and their regulation in potato, particularly in response to elevated temperatures.